Synthesis of C2‐Functionalized Pyrimidine Derivatives by Using Arynes and Dithiopyrimidines - Yang, Chun‐Hong; Wang, Wen‐Peng; Li, Ming; Gao, Fan; Ma, Wen; Chen, Dong‐Ping; Wang, Xi‐Cun; Quan, Zheng‐Jun (European journal of organic chemistry, 2023)
C2‐functionalized pyrimidine derivative is a family of important nitrogen heterocyclic compounds due to their unique structure and multiple reaction sites. In this work, a novel method for the synthesis of C2‐functionalized pyrimidine derivatives through phenylalkynes and pyrimidine disulfides under ambient conditions is proposed. The reaction can be triggered by adding catalytic amounts of cesium fluoride, which is characterized by free‐catalyst and special activator. Importantly, this reaction has good compatibility with substrates substituted by electron‐donating and electron‐withdrawing groups at C4. Density functional theory (DFT) calculations also indicates that the production of C2‐functionalized pyrimidine derivatives is more favourable. A method for synthesizing C2 functionalized pyrimidine derivatives by phenylalkyne and pyrimidine disulfide under environmental conditions with good group compatibility is reported. Furthermore, density functional theory (DFT) calculations confirm that it is more advantageous to generate C2‐functionalized pyrimidine derivatives.